Investigation of Influence of MQL Machining Parameters on Cutting Forces During MQL Turning of Carbon Steel St52-3. (2015) - Ekinovic, S.; Prcanovic, H.; Begovic, E.
Abstract: Basic information concerning a Minimum Quantity Lubrication (MQL) machining is presented in the paper. Generally speaking, there are two groups of MQL machining with respect of aerosol composition classification. First group represents the aerosol as an air-oil mixture, and second group represents so called advanced MQL systems uses aerosol that includes not only oil but also some other components. There are two examples of advanced MQL systems: oil-on-water droplet and advanced minimum quantity cooling lubrication machining (MQCL machining). Investigation of influence of MQL (oil-on-water droplet system) machining parameters on cutting forces during MQL turning of carbon steel St52-3 is presented in this paper. Quantity of oil (10 to 50 ml/h), water (0.3 to 1.7 l/h) and position of nozzle (rake plane and clearance plane side of the tool) were factors which influence explored. Experimental results show the appearance of minimum cutting force during machining with 1.7 l/h of water, and 10 ml/h of the oil. Also, cutting forces are 17% smaller the same ones during machining without coolant and lubricant.